The Dark is Rising: Contrasting the Dark Triad and Light Triad on Measures of Political Ambition and Participation - Peterson, Rolfe Daus; Palmer, Carl L. (Frontiers in Political Science, 2021)
A growing body of research suggests a significant relationship between dark personality traits and political behavior. While the personality characteristics of Machiavellianism, narcissism, and psychopathy (labeled the Dark Triad) have been associated with a range of political attitudes, research has not tested the Dark Triad in combination with the emerging use of the comparable Light Triad of personality. This paper sets up an exploration of the competing influences of light and dark personality traits on political participation and ambition. Our analyses corroborate that Dark Triad traits are significantly related to ambition and political participation. Though the dark personality traits remain predominant, consistent with prior research, there are significant effects for some Light Triad traits as well. Our findings have implications for a deeper understanding of the mix of personality traits that drive political ambition and participation, expanding upon the normative discussion of who is, in fact political.